2005
DOI: 10.1542/peds.2004-0059
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Respiratory Syncytial Virus Bronchiolitis Is Affected by Cigarette Smoke Exposure and Atopy

Abstract: ABSTRACT. Objective. Respiratory syncytial virus (RSV) bronchiolitis is a common cause of hospitalizations in children and has been increasingly identified as a risk factor in the development of asthma. Little is known about what determines the severity of RSV bronchiolitis, which may be helpful in the initial assessment of these children.Design. We evaluated a variety of environmental and host factors that may contribute to the severity of RSV bronchiolitis in the RSV Bronchiolitis in Early Life prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
129
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 31 publications
(30 reference statements)
16
129
1
6
Order By: Relevance
“…5 Bradley et al found age as a significant factor in severity of infection; the younger the infant, the more severe the infection. 11 Sex distribution of the patients (male:female; 1.9:1) was almost similar to the study of Bashar et al who found male to female ratio 1.8:1 whereas Kabir et al showed male:female ratio 2.7:1.…”
Section: Discussionsupporting
confidence: 84%
“…5 Bradley et al found age as a significant factor in severity of infection; the younger the infant, the more severe the infection. 11 Sex distribution of the patients (male:female; 1.9:1) was almost similar to the study of Bashar et al who found male to female ratio 1.8:1 whereas Kabir et al showed male:female ratio 2.7:1.…”
Section: Discussionsupporting
confidence: 84%
“…Factors underlying the frequency and severity of episodes are only partially understood, but the severity of the first episode (which is, in turn, related to pre-existent impaired lung function and younger age), atopy, prematurity and exposure to tobacco smoke have been implicated [29][30][31][32][33][34][35]. Whether or not [36][37][38].…”
Section: Definitionsmentioning
confidence: 99%
“…(Papenburg et al, 2012) In a study examining infants admitted to the hospital in St. Louis, exposure to post-natal cigarette smoke from the mother, younger age, and Caucasian race in contrast to black race were all predictors of more severe RSV bronchiolitis. (Bradley et al, 2005) …”
Section: Epidemiology Of Human Rsv Bronchiolitismentioning
confidence: 99%